Implementation Of Halal Fashion Education To Build Muslim Identity In Students Of Luqman Hakim Islamic Boarding School - Nabilla Zalfa Azzahra; Saskia Rahma Yuniarti; Natasya Hildayatu Naila; Ishmatuddiana; Hendri Hermawan Adinugraha (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2025)
Modern fashion trends often pose a dilemma for young Muslims in balancing style and adherence to sharia. Education about halal fashion is important, especially in the pesantren environment as a center for the formation of Islamic character. This research raises the implementation of halal fashion education for students of the Luqman Hakim Islamic Boarding School as a strategy to form a solid and relevant Muslim identity. The method of activity includes counseling, discussion, and direct practice of recognizing and choosing clothes according to sharia principles. The results show that there is an increase in students' understanding of the concept of halal fashion as well as a change in attitudes in dressing that is more Islamic and reflects religious values. This program not only builds spiritual awareness, but also instills Islamic aesthetic values and opens up opportunities in the development of a creative economy based on Islamic values. Halal fashion education has proven to be an effective approach in fostering a generation of Muslims who are characterful, creative, and competitive.